If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 12 = -10 Reorder the terms: 12 + Y = -10 Solving 12 + Y = -10 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + Y = -10 + -12 Combine like terms: 12 + -12 = 0 0 + Y = -10 + -12 Y = -10 + -12 Combine like terms: -10 + -12 = -22 Y = -22 Simplifying Y = -22
| Y+1.05+7.26= | | z-3.76=79.1 | | 8(-2x-4)12=-52 | | 2.4+5(2.4-1)=7 | | 5x+9=8x+12 | | -21+x=-85 | | (-14i)(-8i)=0 | | 68x-2=(50x+4)+15x | | 6y+3+3y-5= | | 5(1n-1)=7 | | 6=z/4-3 | | 11-5+5/-2 | | (8x+5)(8x+5)=4 | | 5y-2=2y-19 | | 431x=3574299 | | -2.3=u/4+4.1 | | 2(x+5)=10x-14 | | -35=x-5 | | 2=2+5v+2v | | -5-n=10 | | -3+12+6= | | 0.78=logx | | 8(x+1)=7(x+2) | | 2/7(21) | | 7(x-3)=8(4-2x) | | 5x-1=6x+7 | | 7(x-2)=-5 | | (2x+1)(3x-9)=0 | | 68x-25=(50x+4)+15x | | 52=3(-n-8)-2(1-8n) | | 47-y=205 | | 3n+6/3=5 |